Local memory CD4 T cell niches in respiratory viral infection - Pruner, Kurt B.; Pepper, Marion (The Journal of experimental medicine, 2021)
Respiratory viral infections present a major threat to global health and prosperity. Over the past century, several have developed into crippling pandemics, including the SARS-CoV-2 virus. Although the generation of neutralizing serum antibodies in response to natural immunity and vaccination are considered to be hallmarks of viral immune protection, antibodies from long-lived plasma cells are subject to immune escape from heterologous clades of zoonotic, recombined, or mutated viruses. Local immunity in the lung can be generated through resident memory immune subsets that rapidly respond to secondary infection and protect from heterologous infection. Although many immune cells are required to achieve the phenomenon of resident memory, herein we highlight the pleiotropic functions of CD4 tissue resident memory T cells in the lung and discuss the implications of resident memory for vaccine design.